Nutrient intake and food consumption of adolescents and young adults with phenylketonuria - Schulz, Bettina; Bremer, Hans J. (Acta paediatrica, 1995)
Food and nutrient intake was assessed in 99PKU patients (12-29 years old) by two food protocols (7 days and 4 days, respectively). Ninety-three patients completed at least one 7-day food record and 83 both records. Nineteen of 93 patients had already stopped taking the phenylalanine-free amino acid mixture (AAM), which is enriched with vitamins, minerals and trace elements. Plasma phenylalanine levels in this group were significantly higher than in patients who were still taking the AAM. Even without the AAM, protein intake still met the recommendations, but thiamin, riboflavin, folate, calcium and iron levels were below 80% of the US RDA in most patients. For those still taking the AAM, calorie, protein, vitamin and mineral intakes were above the recommendations. The diet was characterized by a low intake of fiber (median 14 (range 8-35)g/day), fat (27 (10-47) cal%) and cholesterol (75 (13-417) mg/day) as well as a high ratio of polyunsaturated/saturated fatty acids (0.7 (0.2-2.4)). Problems with dietary compliance in adolescents and young adults may lead to a combination of marginal nutrient intake and high phenylalanine levels. ? Adolescence, adulthood, dietary intake, nutrients, phenylketonuria
Gesehen am 29.05.2024